IN HOUSE TRAINING (IHT) MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN RPP MERDEKA BELAJAR - Titik Suhartini (Universitas Ngudi Waluyo, 2021)
Lesson plan or RPP is a form of learning planning that will be carried out by educators in learning activities. This fact shows that not all teachers have sufficient competence in making lesson plans (RPP). Effort In essence, increasing teacher competence can be done through various types of activities or by various methods and strategies. One way that can be done to improve teacher competence is the In House Training (IHT) activity. The goal to be achieved in this school action research activity is to find out how to improve the competence of SDN 5 Temulus teachers to prepare lesson plans for merdeka belajar through In House Training (IHT) activities. The research used in House Training RPP merdeka belajar. The results of data analysis showed an increase in teacher competence in making lesson plans (RPP), in the initial conditions 17% of competence was in the good category, 17% was in the sufficient category and 66% was still in the poor category. After being given action in the form of House Training activities, the teachers increased in the first cycle to 66% of teachers in the good category and 34% of the teachers in the sufficient category, and in the second cycle to 5 teachers (83%) who attended the in House Training in the good category, and 1 teacher ( 17%) in the sufficient category.